CAM GROOVE LINEAR AND KINEMATICS RESEARCH OF ROTATING-SLEEVE DISTRIBUTING-FLOW SYSTEM - XU Wei; ZHANG HongXin; ZHANG TeiZhu; GAO Lei; ZHANG YanJun (Jixie qiangdu)
According to the problems that loose structure,large throttling loss and Efficiency is affected by the operating frequency,when reciprocating plunger pump uses valve type orifice structure.Rotating-sleeve distributing-flow system for reciprocating plunger pump was put forward,which has the advantages of simple and compact structure,small throttling loss,stable work and assignment without delay.Described the working principle of rotary sleeve type flow system,established the kinematics model of three different cam groove liner,analyzed kinematics characteristics influence of distributing-flow system that three cam groove type rotating-sleeve effect on,and analyzed the shear strength of the drive pin.The numerical results showed that compared with the other two linear cam grooves,the angular velocity and angular acceleration of sinusoidal cam groove rotating-sleeve has smallest size and magnitude,and has no inflection point and step,and the rotating-sleeve can rotates relatively stable,the impact force of each parts of distributing-flow system is smallest.